Confirming—and testing—bonds of trust: A mixed methods study exploring community health workers’ experiences during the COVID-19 pandemic in Bangladesh, Haiti and Kenya - Pooja Sripad; Ann Gottert; Timothy Abuya; Alain Casseus; Sharif Hossain; Smisha Agarwal; Charlotte E. Warren (PLOS Global Public Health, 2022)
Amidst the COVID-19 pandemic and national responses, trust (one’s belief that a system acts in one’s best interest) is important to consider. In community health systems, trust is embedded in relationships between clients, CHWs, and health system stakeholders. This mixed-methods study explores trust through the evolving COVID-19 crisis in Bangladesh, Haiti, and Kenya, where multi-country community health research was underway. We investigate the extent and ways trust between communities, community health workers (CHWs), and health system actors shift, including its relation to community fear and hostility, through self-reported positive and negative experiences of CHWs and policy/program stakeholders on a phone-based survey with 2,025 CHWs and 72 key informant interviews, including CHWs, in late 2020. On surveys, CHWs reported high levels of community trust (8/10 in Bangladesh and Kenya; 6/10 in Haiti) with over 60% reporting client relief in seeing their CHWs. About one-third of CHWs across countries reported experiencing instances of hostility from community members during the pandemic in the form of refused home-entry, ignored advice, or being shouted at. Multivariate analyses revealed that CHWs reporting more positive and fewer negative experiences is consistently associated with continuing routine work, doing COVID-19-related work, and greater community trust. Qualitative interviews showed that existing pre-pandemic trusting relationships withstood the early phase of COVID-19, mitigating negative community reactions toward CHWs and stigma towards COVID-positive individuals, maintaining routine health services, and sustaining appreciation for CHW-provided prevention information and emotional support. CHW-community and CHW-health system actor trust is strengthened when CHWs are well-resourced; CHW-community trust is strained by public frustration at the pandemic, associated restrictions, and sociopolitical stressors. Our study suggests that with adequate institutional support, bonds of trust can promote resilient community health systems during extended public health crises, through CHWs’ commitment to mitigating misinformation, reducing stigma, maintaining routine service provision, and promoting COVID-19 prevention.